2020
DOI: 10.1186/s41936-020-00156-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces regeneration of β cells and suppression of phosphorylated-NF-κB in streptozotocin-induced diabetic mice

Abstract: Objectives This study aimed to assess the immunomodulatory effect of curcumin on innate and adaptive immune responses, as well as its inhibitory power on hyperglycemia in streptozotocin (STZ)-induced diabetic CD1 mice. Material and methods Mice were divided into six groups as follows: normal control mice (I), mice were intraperitoneally (i.p.) injected with either citrate (II), DEMSO (III), or curcumin (170 mg/kg, 3 times/week, for 28 days) (IV), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Ascetic fluid is the main source of nutrition for carcinoma development. The accumulation of ascetic fluid in the peritoneal cavity was either because of proliferation of tumor cells or the decrease in lymphatic recovery system 37 …”
Section: Discussionmentioning
confidence: 99%
“…Ascetic fluid is the main source of nutrition for carcinoma development. The accumulation of ascetic fluid in the peritoneal cavity was either because of proliferation of tumor cells or the decrease in lymphatic recovery system 37 …”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds in various forms, such as berberine, curcumin, and mangiferin as well as extracts of medicinal plants have been found to have protective and regenerative effects on β-cells [36] . For instance, a recent study showed that curcumin had anti-diabetic effects as it could help to regenerate β-cells in vivo by the immunomodulatory effect on T helper1-related cytokines (IL-2) as well as the immunosuppressive action on IFN-γ, IL-6, and IL-1β [37] . Other study showed that intraperitoneal injections of turmeric ( Curcuma lo nga) extract, which is the main source of curcumin, could significantly reduce blood glucose level from around 400–100 mg/dL and showed protective effects on pancreatic and renal structure and function [38] .…”
Section: Resultsmentioning
confidence: 99%
“…43,44 A study on diabetic mice revealed that through the immunomodulatory impact on T helper1-related cytokines and the immunosuppressive activity on pro-inflammatory cytokines, curcumin (170 mg per kg, three times a week) can ameliorate damage to pancreatic cells. 45 In an additional study, 10 mg kg −1 day −1 of curcumin supplementation within a course of 42 days reduced inflammation and fibrosis by obstructing the P38 and AKT signal pathways as well as suppressing hyperglycemia-induced inflammation. 46 Kim et al (2016) revealed that curcumin prevents the accumulation of renal lipids and oxidative stress through the AMPK and Nrf2 signaling pathways, exerting renoprotective effects.…”
Section: Reviewmentioning
confidence: 96%
“…56 Therefore, curcumin-induced PPARγ has a protective effect against abnormal cellular glucose levels and AGE accumulation, which are two important consequences of diabetes. Furthermore, curcumin can prevent or delay T2DM by increasing insulin secretion, 22 improving β-cell function, 45 preventing β-cell death, 3 increasing adiponectin levels, and decreasing C peptide levels along with insulin resistance. 80 Also, it can modulate lysosomal enzyme activities in diabetes.…”
Section: Molecular Mechanisms Of the Anti-diabetic Effects Of Curcumi...mentioning
confidence: 99%